Status of Mortgage Rights on Building Use Rights on Land Whose Term Has Expired - Wahyudi, Syafrizal; Yusri, Yusri; Fitri, Ria (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
Article 18 paragraph (1) of Law No. 4/1996 states that Mortgage Rights are extinguished due to debt repayment, relinquishment by the holder, court order, or extinguishment of land rights. In Batam City, there is a case of a Building Rights Title (SHGB) being used as collateral, but its validity period has expired, and the debtor has not fulfilled their obligations. This research aims to analyze the status and position of Mortgage Rights on an object with an expired Building Rights Title under Indonesian Positive Law, the legal consequences for the holder of the Mortgage Rights on an expired Building Rights Title, and the legal protection for the creditor when the Building Rights Title, as the object of the mortgage, is not extended or renewed. This is normative legal research using the statutory and case approach methods. Data is obtained through literature studies, interviews, and documentation, analyzed using qualitative methods. Mortgage rights are considered extinguished unless the creditor or debtor extends them through a Deed of Mortgage (APHT). The expiration of Mortgage Rights results in the land becoming state property unless it is extended by the debtor or creditor. The expiration of Mortgage Rights does not erase the debtor’s debt, but the creditor's position changes from preferred to concurrent, meaning the creditor no longer has priority in repayment. Creditor protection can be achieved through negotiation for an extension or renewal of the SHGB. If this fails, the bank can sell the mortgage underhand, auction the mortgage, file for bankruptcy, or file a lawsuit. It is recommended that further regulation in the Mortgage Rights Law (UUHT) be established regarding the expiration of Building Rights Titles encumbered with Mortgage Rights.